Zinc and selenium modulate barium-induced oxidative stress, cellular injury and membrane-bound ATPase in the cerebellum of adult rats and their offspring during late pregnancy and early postnatal periods. (27th May 2018) - Elwej, Awatef; Ghorbel, Imen; Chaabane, Mariem; Soudani, Nejla; Mnif, Hela; Boudawara, Tahia; Zeghal, Najiba; Sefi, Madiha
Abstract: Context: Barium (Ba) may induce oxidative stress leading to tissues injury. Objective: Our study investigated the therapeutic efficiency of zinc (Zn) and selenium (Se) against neurotoxicity induced by Ba in adult rats and their progeny. Material and methods: Pregnant rats are exposed either to Ba (67 ppm), Ba + Zn, Ba + S or to only Zn and Se. Results: In Ba-treated rats, there was an increase of MDA, H2 O2, AOPP levels and SOD activity in the cerebellum of dams and their pups, a decrease in GPx, CAT, AChE, Na + K + -ATPase and Mg 2+ -ATPase activities, GSH and NPSH levels. These changes were confirmed by histological damages. Co‐administration of Zn or Se to Ba-treated rats ameliorated the biochemical and histological aspects. Conclusion: Our results revealed that Zn and Se have shown promising effects against Ba toxicity in the cerebellum of adult rats and their suckling pups.